2010
DOI: 10.1117/1.3290822
|View full text |Cite
|
Sign up to set email alerts
|

Integration of single-fiber reflectance spectroscopy into ultrasound-guided endoscopic lung cancer staging of mediastinal lymph nodes

Abstract: Abstract. We describe the incorporation of a single-fiber reflectance spectroscopy probe into the endoscopic ultrasound fine-needle aspiration ͑EUS-FNA͒ procedure utilized for lung cancer staging. A mathematical model is developed to extract information about the physiological and morphological properties of lymph tissue from singlefiber reflectance spectra, e.g., microvascular saturation, blood volume fraction, bilirubin concentration, average vessel diameter, and Mie slope. Model analysis of data from a clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 24 publications
0
50
0
Order By: Relevance
“…Here, a Direct Fit PTI (DF-PTI) model was developed and employed with seven main modifications to the previous model [12]: 1) to improve fit quality at all wavelengths, the semi-empirical model was fit directly to the measured data without a "canonical normal" spectrum, 2) the wavelength range for fitting was expanded from 700 nm to 750 nm to more accurately account for the effect of cellular nuclear size and refractive index on spectrum shape [17], 3) the cost function was minimized with a nonlinear least-squares iterative algorithm, 4) bilirubin [Bilirubin] was added as an absorber [11], 5) collagen concentration [Collagen] and cellular density [Cell] were freely varied, 6) nuclear refractive index was freely varied, as the refractive index is related to tissue malignancy [18], and 7) the mean vessel radius R v was freely varied [19]. In the original PTI model, mean vessel radius was fixed at 7 µm and the absorption coefficient of whole blood was employed for the vessel packaging correction factor.…”
Section: Direct Fit Pti Model For Steady-state Reflectance and Fluorementioning
confidence: 99%
See 1 more Smart Citation
“…Here, a Direct Fit PTI (DF-PTI) model was developed and employed with seven main modifications to the previous model [12]: 1) to improve fit quality at all wavelengths, the semi-empirical model was fit directly to the measured data without a "canonical normal" spectrum, 2) the wavelength range for fitting was expanded from 700 nm to 750 nm to more accurately account for the effect of cellular nuclear size and refractive index on spectrum shape [17], 3) the cost function was minimized with a nonlinear least-squares iterative algorithm, 4) bilirubin [Bilirubin] was added as an absorber [11], 5) collagen concentration [Collagen] and cellular density [Cell] were freely varied, 6) nuclear refractive index was freely varied, as the refractive index is related to tissue malignancy [18], and 7) the mean vessel radius R v was freely varied [19]. In the original PTI model, mean vessel radius was fixed at 7 µm and the absorption coefficient of whole blood was employed for the vessel packaging correction factor.…”
Section: Direct Fit Pti Model For Steady-state Reflectance and Fluorementioning
confidence: 99%
“…Advantages of optical spectroscopy compared to current imaging modalities (listed above) include quantifying tissue morphological and biochemical alterations occurring at the molecular and cellular levels during neoplastic progression [10] and clinical compatibility with EUS-FNA procedures [11]. Previously, our group successfully distinguished human pancreatic diseases, including pancreatic adenocarcinoma (AC) and chronic pancreatitis, from normal tissues with multimodal optical spectroscopy and a mathematical photon-tissue interaction (PTI) model [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…As such, SFR spectroscopy may be well suited for detection of localized changes to tissue microstructure that are expected to accompany early onset of disease. Additionally, the compact and simple probe design allows easy incorporation of small-diameter SFR probes into many clinical tools, such as endoscopic catheters (7,8) and FNA-needles (9,10) Recently, our group has shown that the tissue absorption coefficient, µ a [mm -1 ], can be accurately quantified without prior knowledge of the tissue scattering properties from a SFR measurement through the use of empirical models for the effective photon path-length and the collected single fiber reflectance in the absence of absorption (11). Decomposition ii i 0.0 of µ a into the constituent absorption spectra of known tissue chromophores enables accurate measurement of chromophores concentration and microvascular parameters such as local blood oxygen saturation, blood volume fraction, and mean vessel diameter, which can be used for differentiating between healthy and cancerous tissue (10).…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to similar steady-state approaches [1][2][3][6][7][8], the "average" absorption in a larger volume is measured, not just what is immediately in front of the fiber. Extraction of the scattering coefficient, providing structural information, may be possible in sufficiently homogeneous materials but would require careful calibration of the equipment.…”
mentioning
confidence: 99%
“…Minimally invasive in vivo spectroscopy based on needle-guided optical fibers is an attractive tool for medical applications, from tissue diagnostics in general to characterization of suspect tissue lesions [1][2][3][4][5][6][7][8]. Ensuring that spectroscopic signals are representative of the tissue studied is of major concern, and it is not a simple matter.…”
mentioning
confidence: 99%